A labVIEW-based remotely controllable and accessible laboratory platform for communication systems II lecture experiments - (:unkn) unknown (Gazi Universitesi, 2014)
In this study, a remotely accessible and controllable communication systems laboratory model is designed for the undergraduate Electronics and Communication Engineering Education. This laboratory model is designed by using LabVIEW program as real time and virtual for Communication Systems II lecture laboratory applications that contain Convolutional Codes, Viterbi Decoding Algorithm Method, phase shift keying modulated / demodulated schemes and system performance experiments. The student can perform these experiments in the remotely accessible and controllable laboratory platform in campus. This laboratory environment is established by using a server PC with LabVIEW program, Agilent 33220A signal generator, Data Acquisition Card (NIDAQ -PAD 6015). A web site contains the virtual / real time experiments, experiment sheets, and theoretical information documents of all experiments is designed to access this laboratory platform. In addition, a web page is designed for the teacher to observe and communicate with the students simultaneously, while performing their experiments. The students can access laboratory at the web site http://localhost/Online LabVIEW/default.aspx in campus. This interactive laboratory platform facilitates to bring in practical skills for students as well as intensify the theoretical studies. The objective of this study is to establish the real-time web-based laboratory platform conduction by accessing the laboratory set-up from a remote location and observe the experimental parameters by generating the control commands at a distant client.
Keywords: Communication systems model; Electronics and communication undergraduate education; LabVIEW; Web-based laboratory